Nanotechnology: A Gentle Introduction to the Next Big Idea - Ratner, Mark; Ratner, Daniel (Pearson, 2002)
Nanotech for everyone! The friendly, non-technical guide to the next industrial revolution. Discover the world's next $1 trillion industry! The easy-to-understand guide to nanoscale technology, science, business, and ethics Today's hottest nanotech research and tomorrow's hottest applications Nanobots, quantum and DNA computing, nanosensors, neuro-electronic interfaces, and much more Insider's assessment of the nanotechnology marketplace and investment opportunities By 2015, nanotechnology could be a $1 trillion industry. Now, renowned nanotech pioneer Mark Ratner and technology entrepreneur Daniel Ratner show you how nanotech works, why it's so exciting, what's new, and what's next. They survey the entire field-technology and business-covering nanobots, molecular electronics, quantum computing, biostructures, nanotubes, molecular motors, nanosensors, and many other breakthrough applications. They provide easy-to-understand explanations of every key concept, plus dozens of visuals that bring nanotechnology to life. Coverage includes: A simple, brief, almost math-free introduction to nanotech science "Grand tour" of nanotech R&D, from "smart materials" to DNA computing Breakthrough biomedical applications, including neuro-electronic interfaces and new drug delivery systems Current and emerging nanotech systems for optoelectronics and communications Nanotech here and now: nano-enhanced tennis balls, suntan lotions, and other products already in the market A realistic assessment of nanotech investment opportunities for the short- and long-term Ethical issues associated with nanotech research and product development.